Corporate Governance and Voluntary Human Capital Disclosure of Quoted Deposit Money Banks in Nigeria - Ojo, Lukman Olatunji; Umar, Abdullahi Adudu (FUDMA Journal of Accounting and Finance Research [FUJAFR], 2024)
The study examines the factors influencing human capital disclosure in corporate reports of 14 Nigerian deposit money banks. The research used secondary data from annual reports from 2014 to 2023, and the logistics regression was used for data analysis. The results showed that managerial ownership positively affects human capital disclosure, leading to higher disclosure levels. This result aligns with previous studies showing a positive relationship between managerial ownership, institutional ownership, board financial expertise, board independence and human capital disclosure. The study concludes that managerial ownership is a viable corporate governance mechanism for improved voluntary disclosures. Signaling the market positively and encouraging executive directors to focus on long-term viability and product quality. The study suggests that board financial expertise positively impacts human capital disclosure (HCD), suggesting that understanding accounting principles and financial statements can improve board oversight and shareholder interests. It recommends companies to improve human capital disclosures in corporate reports, adopt robust methodologies, and encourage voluntary disclosure of value-added human resource activity.